CLIMATE CHANGE AND FOREST ECOSYSTEMS: IMPACTS AND ADAPTATION STRATEGIES - Choi Seojin; Kim Minho; Lee Jiwon (Journal of Selvicoltura Asean, 2025)
Climate change is one of the most critical challenges facing global ecosystems, with forest ecosystems being particularly vulnerable to its impacts. The alteration of climate patterns, such as increased temperatures, altered precipitation patterns, and extreme weather events, has led to significant disruptions in forest biodiversity, carbon storage, and ecosystem services. This study investigates the effects of climate change on forest ecosystems and explores potential adaptation strategies to mitigate these impacts. The primary objective of this research is to assess the impacts of climate change on forest ecosystems and identify viable adaptation measures to ensure ecosystem resilience. This research employs a combination of qualitative and quantitative methods, including field observations, data analysis from climate models, and review of existing literature on forest ecology and climate adaptation strategies. The findings indicate that climate change has led to shifts in species distribution, changes in forest composition, and increased susceptibility to pests and diseases. Additionally, forest degradation and loss of biodiversity have been observed in several regions. Adaptation strategies, such as assisted migration, improved forest management practices, and conservation efforts, have shown potential to enhance the resilience of forest ecosystems. In conclusion, while climate change poses significant threats to forest ecosystems, proactive adaptation strategies can mitigate some of the adverse effects. It is essential to integrate climate change considerations into forest management policies to promote long-term ecosystem sustainability.